Faktor-Faktor yang Berhubungan dengan Nyeri pada Pasien Low Back Pain di Poliklinik Saraf Rumah Sakit Islam Sultan Agung Semarang - Badriyah, Badriyah; Ahmad Ikhlasul Amal; Dwi Retno Sulistyaningsih (Pusat Riset dan Inovasi Nasional, 2025)
Low Back Pain (LBP) is one of the most common musculoskeletal health problems experienced by various age groups and can significantly affect quality of life and reduce patient productivity. LBP is often associated with multiple risk factors, both biological, psychological, and social, thus requiring special attention in terms of management and prevention. This study aims to analyze the factors associated with pain levels among LBP patients at the Neurology Clinic of Sultan Agung Islamic Hospital Semarang. This research employed an observational design with a cross-sectional approach. The study sample consisted of 100 patients selected using a total sampling technique according to inclusion criteria. Data were collected through structured interviews and questionnaires covering respondents’ demographics, medical history, physical activity, body mass index (BMI), and pain level assessment. The results showed that the majority of patients were female (53%) and aged ≤50 years (74%). Most respondents had moderate physical activity levels (75%) and normal BMI. Bivariate analysis revealed a strong relationship between age, physical activity, and pain level, while gender showed a moderate relationship with pain intensity. Occupational factors were also found to influence patients’ pain perception. These findings indicate that age, gender, physical activity, BMI, and occupation are important variables associated with pain in LBP patients. Therefore, promotive, preventive, and rehabilitative interventions focusing on physical activity regulation, healthy lifestyle education, and early detection of risk factors are recommended to improve the quality of life of patients with LBP.